Indonesia: Out of One, Many? - Ruth-Heffelbower, Duane (Tufts Archival Research Center, 2005)
Volume 26, Issue 2. Summer/Fall The inexorable movement toward democracy in Indonesia is threatening the countryï¿½s territorial integrity. As people become less willing to follow central government orders in the post-Soeharto era, the desire to escape government interference grows.